Development of dna aptamers for hemolysin e antigen of salmonella enterica serovar typhi towards diagnostic application - Mohamad, Ahmad Najib (2025)
The rapid and accurate diagnosis of typhoid fever using specific biomarkers is essential for enhancing treatment outcomes and preventing disease transmission. This study aimed to develop a DNA aptamer-based detection system for Salmonella enterica serovar Typhi (S. Typhi), focusing on the hemolysin E (HlyE) antigen. Using Systematic Evolution of Ligands by EXponential enrichment (SELEX), DNA aptamers targeting the HlyE antigen were isolated and evaluated for binding affinity and specificity through enzyme-linked oligonucleotide assay (ELONA). Following SELEX, 11 aptamers were identified, and three (AptHlyE97, AptHlyE11 and AptHlyE45) were selected for further characterization. Their dissociation constants (Kd) fell within the nanomolar range, with AptHlyE97 showing the highest binding affinity at 83.6 nM, followed by AptHlyE11 at 102.2 nM and AptHlyE45 at 119.3 nM. Specificity tests demonstrated that these aptamers could effectively distinguish S. Typhi HlyE from other bacteria, including Salmonella Paratyphi A (P<0.001), Salmonella Paratyphi B (P<0.001), Shigella flexneri (P<0.001), Klebsiella pneumoniae (P<0.001) and Escherichia coli (P<0.001). Molecular docking analysis further supported these findings, with AptHlyE97 displaying the highest binding energy (-15.5 kcal/mol). Molecular dynamics simulations confirmed the aptamer-antigen stability, with a root-mean-square deviation (RMSD) of ~2.0 Å during 100 ns simulations. AptHlyE97 was subsequently used to develop an electrochemical aptasensor as a proof-of-concept diagnostic tool. The aptasensor was constructed by immobilizing AptHlyE97 onto a screen-printed gold electrode (Au-SPE) via thiol conjugation, with potassium ferricyanide and ferrocyanide employed for signal detection. The aptasensor demonstrated excellent diagnostic performance, achieving 100% sensitivity and 85.7% specificity in serum sample testing. Additionally, it exhibited a strong linear response with a limit of detection (LoD) of 0.158 ng/mL. This study presents a novel aptamer specific against HlyE antigen of S. Typhi and aptamer-based diagnostic platform for the efficient and selective detection of S. Typhi HlyE antigen. The high sensitivity, specificity and low detection limit of the developed aptasensor highlight its potential for advancing point-of-care diagnostics, particularly in resource-limited settings. This innovation lays a solid foundation for improving typhoid fever detection and management, offering a promising tool for community-level disease monitoring and control